A short report of novel RARG-HNRNPM fusion gene in resembling acute promyelocytic leukemia. Issue 1 (31st December 2022) - Song, Yang; Hou, Jiangxue; Wan, Li; Liu, Kaiqi; Zhou, Chunlin; Wei, Shuning; Zhang, Guangji; Lin, Dong; Li, Yan; Fang, Qiuyun; Liu, Yuntao; Gong, Benfa; et al.
ABSTRACT: Background: Resembling acute promyelocytic leukemia (APL) is a unique subtype of APL who sharing clinical, morphological, and immunophenotypic features with typical APL, but lacking evidence of PML-RARA fusion gene and usually insensitive to arsenic trioxide (ATO) and all-trans retinoic acid (ATRA). For years, RARA, RARB and RARG rearrangement were found in resembling APL continually. The confirmed partner genes of RARG rearrangement included CPSF6, NUP98, NPM1, PML, and HNRNPC . These patients were a group of resembling APL with rare molecular genetic abnormality and unfavorable prognosis. They usually were resistant to ATO and ATRA but partially sensitive to anthracycline-based chemotherapy. Case presentation: We reported a 25-year-old female patient with a novel fusion gene RARG-HNRNPM (RARG chr12:53606869: –; HNRNPM chr19: 8527413: + based on GRCh37/hg19 Assembly) through RNA-seq as resembling APL. The patient with RARG-HNRNPM was benefited from a combined chemotherapy homoharringtonine, cytarabine, and aclacinomycin (HAA) regimen with no relapse. Discussion and conclusions: RARG rearrangement resembling APL are various. The treatment should be switched from ATRA/ATO to AML combined chemotherapy regimen early.